Efeito do manejo da água e de herbicidas na cultura do arroz (Oryza sativa L.) irrigado - Medeiros, Roberto Dantas de; Ghelfi Filho, Hugo; Dario, Geraldo J. Aparecido; Botrel, Tarlei Arriel; Costa, Maristélio da Cruz (IRRIGA, 1997)
Efeito do manejo da água e de herbicidas na cultura do arroz (Oryza sativa L.) irrigado